Paralympic Games: History and legacy of a global movement - Legg, D. (Physical Medicine & Rehabilitation Clinics of North America, 2018)
The Paralympic Games have an interesting history that began after World War II. The Games and movement have been impacted by and have had an impact on society and the larger able-bodied sport system. The future of the Games and movement is also further impacted by larger cultural shifts, and the Games themselves have potentially left lasting legacies for the host cities and persons with impairment worldwide.